Detection and Evaluation of Solar Panel Energy Through Light Intensity Level - Kamaruzaman, Nur Faizah; Khairul Anuar Mohamad, (Evolution in Electrical and Electronic Engineering, 2022)
Solar energy can only be produced in the presence of the sun. The only source of power at night is what was generated during the day and stored in batteries. The light intensity of the available solar irradiation is also impacted by environmental problems like weather changes and orientation. Therefore, the goal of this study is to assess the energy of solar panels by measuring the amount of available light intensity. To improve the efficiency of solar panels, the amount of light generated in three different orientations is evaluated to determine which ones take in the most sunlight. The developed device is equipped with LDRs, LEDs and a temperature sensor. Each direction has its own LCD set up to record and display data on voltage, current, temperature, and energy produced. The findings indicate that a voltage divider could be used to calculate current and voltage and that LEDs light up when the system reaches a predetermined threshold value. The energy of a solar panel is higher when it receives higher light intensity. According to measurements, the LDR oriented toward the east receives the most solar irradiation and the temperature sensed is higher at peak hours. To summarize, the objectives are successfully achieved in this project.